2016
DOI: 10.1099/mic.0.000332
|View full text |Cite
|
Sign up to set email alerts
|

Developmental defect of cytochrome oxidase mutants of Streptomyces coelicolor A3(2)

Abstract: To study the link between energy metabolism and secondary metabolism/morphological development in Streptomyces, knockout mutants were generated with regard to the subunits of the cytochrome oxidase supercomplex (CcO) in Streptomyces coelicolor A3(2). All mutants exhibited an identical phenotype: viable but defective in antibiotic production and cell differentiation when grown in both complex and minimal media. The growth yield of the CcO mutant was about half of that of the WT strain on glucose medium while bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Phosphorylated regulator affects or regulates the transcriptional level of three downstream genes. This resulted in a transcriptional activation of SACE_0528 and SACE_1321 and inactivation of SACE_2475 respiration that transfers electrons from menaquinol to oxygen, requires Cu 2+ to enhance its activity (Fujimoto et al 2016). In the case of WT-Δ0101 strain, its system most likely allows higher intracellular copper ion concentration, making oxidative phosphorylation more active thus generating more energy.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylated regulator affects or regulates the transcriptional level of three downstream genes. This resulted in a transcriptional activation of SACE_0528 and SACE_1321 and inactivation of SACE_2475 respiration that transfers electrons from menaquinol to oxygen, requires Cu 2+ to enhance its activity (Fujimoto et al 2016). In the case of WT-Δ0101 strain, its system most likely allows higher intracellular copper ion concentration, making oxidative phosphorylation more active thus generating more energy.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of the bcc-aa 3 respiratory branch leads to moderate to severe growth phenotypes in C. glutamicum, while Mycobacterium tuberculosis cannot grow without this branch of the respiratory chain. A recent study (26) has shown that deletions in the genes encoding the bcc-aa 3 supercomplex led to a developmental phenotype in S. coelicolor on certain growth media (26). However, no studies have been undertaken to examine the consequences to the physiology of Streptomyces coelicolor caused by deleting the genes encoding the cytochrome bd oxidase.…”
mentioning
confidence: 99%
“…For example, while deletion of the complete locus shown in Figure 1 restricts, but does not abolish, aerobic growth of the bacterium [Fujimoto et al, 2016;Fischer et al, 2018], the resulting oxidase-negative phenotype of the mutant (strain COE192) can only be restored to an oxidase-positive phenotype when the complete qcr-cta gene locus is supplied on an integrative plasmid [Fischer et al, 2018]. Two genes within this locus, SCO2152 and SCO2153 (Fig.…”
mentioning
confidence: 99%